AI Technologies in Legal Education: Milestones and Signposts for AI Integration - Ignjatovic, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2025)
Abstract: Artificial Intelligence (AI) has prompted change in many walks of life but also generated ample concerns. The application of AI technologies in legal education and practice is still a contentious issue due to the lack of a comprehensive normative framework and structured approach to AI integration. In this context, this paper explores the use of AI technologies in legal education at the international and national levels. After the introductory overview of diverse approaches to AI integration worldwide, the paper first explores the integration practices in developed countries and the current circumstances in Serbia in order to identify good practices which may serve as guidelines in the process of integrating AI technologies in Serbian legal education. Relying on the research results, the second part analyzes how the major AI integration issues have been addressed by law schools in developed countries, particularly in view of instituting viable frameworks for structured, responsible and flexible applications in their legal contexts. Reviewing the key findings, the author discusses the implications, opportunities and considerations for AI integration in Serbian legal education, based on the blended learning and integrated curriculum frameworks aligned with the principles of human-centered, competency-based and pedagogy-driven instructional design